2017
DOI: 10.1007/s00709-017-1161-5
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype reshufflings of Festuca pratensis × Lolium perenne hybrids

Abstract: Many different processes have an impact on the shape of plant karyotype. Recently, cytogenetic examination of Lolium species has revealed the occurrence of spontaneous fragile sites (FSs) associated with 35S rDNA regions. The FSs are defined as the chromosomal regions that are sensitive to forming gaps or breaks on chromosomes. The shape of karyotype can also be determined by interstitial telomeric sequences (ITSs), what was recognized for the first time in this paper in chromosomes of Festuca pratensis × Loli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(62 reference statements)
1
6
0
1
Order By: Relevance
“…Human fragile sites are known as hotspots for chromosome aberrations, especially in many tumor cells [37, 38]. However, in Festuca × Lolium plants, the analysis of the relation between FSs associated with 35S rDNA regions and the location of structural rearrangements revealed that intergenomic changes did not correspond to FSs [39].…”
Section: Discussionmentioning
confidence: 99%
“…Human fragile sites are known as hotspots for chromosome aberrations, especially in many tumor cells [37, 38]. However, in Festuca × Lolium plants, the analysis of the relation between FSs associated with 35S rDNA regions and the location of structural rearrangements revealed that intergenomic changes did not correspond to FSs [39].…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows for the genome-specific chromosome labeling in the cells of allopolyploid or hybrid species. It has been widely used in plant studies to identify putative parental genomes in the interspecific or intergeneric hybrids or allopolyploids (for the review see Chester et al, 2010 ; Silva & Souza, 2013 ), to study the evolution of polyploid genomes ( Song et al, 1995 ; Gaeta et al, 2007 ; Majka et al, 2018 ; Tan et al, 2017 ), or to detect the introgression of alien chromatin ( Schneider et al, 2005 ; Tan et al, 2005 ). It has also become a valuable tool to analyze the meiotic recombination and behavior of chromosomes in the hybrids ( Zwierzykowski et al, 2008 ) as well as translocation ( Kruppa et al, 2013 ), addition ( Molnar-Lang et al, 2000 ; Ji & Chetelat, 2007 ), or substitution ( Pan et al, 2017 ) lines.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue affecting the extent of use of Festulolium in the grass business is the stability of hybrid genomes and the potential for the elimination of chromatin of one of the species in consecutive generations of sexual reproduction. It has been observed that the Lolium chromatin prevails in the Festulolium hybrids (Zwierzykowski et al 1998, Kopecký et al 2006, Książczyk et al 2015, Majka et al 2018a. Zwierzykowski et al (2006Zwierzykowski et al ( , 2011 observed slow and gradual replacement of the Festuca chromosomes by those of Lolium in consecutive generations of F. pratensis × L. perenne hybrids (Fig.…”
Section: Genome Balance and Stability Of Hybridsmentioning
confidence: 95%